The applicability of self-regulation theories in sport: Goal adjustment capacities, stress appraisals, coping, and well-being among athletes. (November 2016) - Nicholls, Adam R.; Levy, Andrew R.; Carson, Fraser; Thompson, Mark A.; Perry, John L.
Abstract: Objectives: We examined a model, informed by self-regulation theories from the health psychology literature, which included goal adjustment capacities, appraisals of challenge and threat, coping, and well-being. Design: Prospective. Methods: Two-hundred and twelve athletes from the United Kingdom ( n = 147) or Australia ( n  = 65), who played team ( n  = 135) or individual sports ( n  = 77), and competed at international ( n  = 7), national ( n  = 11), county ( n  = 67), club ( n  = 84), or beginner ( n  = 43) levels participated in this study. Participants completed measures of goal adjustment capacities and stress appraisals two days before competing. Athletes also completed coping and well-being questionnaires within 3 h of their competition ending. Results: The way an athlete responded to an unattainable goal was associated with his or her well-being in the period leading up to and including the competition. Goal reengagement positively predicted well-being, whereas goal disengagement negatively predicted well-being. Further, goal reengagement was positively associated with challenge appraisals, which in turn was linked to task-oriented coping, and task-oriented coping positively associated with well-being. Conclusion: When highly-valued goals become unattainable, consultants and coaches could encourage athletes to generate alternative approaches to achieve the same goal or help them develop a completely new goal in order to promote well-being among athletes. Highlights: Goal reengagement positively predicts well-being. Goal disengagement negatively predicts well-being. Goal reengagement is positively associated with challenge appraisals. Goal disengagement is negatively associated with threat appraisals. Coping was associated with well-being.